Significance of detection of extra metacentric microchromosome in amniotic cell culture. Issue 2 (April 1978) - Bernstein, R; Hakim, C; Hardwick, B; Nurse, G T
Abstract : A metacentric bisatellited microchromosome was detected in all metaphases from an amniotic culture performed because of maternal age. A wide-ranging survey of the literature failed to disclose any consistent anomaly associated with such a marker, but did reveal that the clinical picture of patients manifesting it could range from complete normality through mental retardation to a variety of deformities. The parents elected for termination, and the only deformity detected in the abortus was fixed talipes equinovarus. The implications of the finding of this marker chromosome on amniocentesis, believed to be reported for the first time here, are discussed particularly in the context of genetic counselling.